Analytical graphs to describe operating status of industrial alarm variables. (January 2022) - Wang, Zhen; Wang, Jiandong
Abstract: A large number of alarm variables are configured to automatically detect the occurrences of abnormalities at complex industrial plants. As abnormalities are absent, occurring, persisting and disappearing, alarm variables go through the normal status, running into the abnormal status, staying in the abnormal status, and leaving the abnormal status. This paper formulates novel analytical graphs to describe the operating status of single and multiple alarm variables. By looking at the analytical graphs, industrial plant operators are aware of the status of alarm variables in a concise and clear manner, instead of via a high-demanding approach by visualizing massive operation data. The analytical graphs are composed of standard and newly-defined status metrics. Typical patterns of analytical graphs are summarized for different status of alarm variables. The effectiveness of formulated analytical graphs is illustrated by numerical and industrial examples.